Lying behaviour of lactating dairy cows in a cow-calf contact system - Wegner, Claire Sydney (2021)
Conventional dairy farming practices usually involve the early separation of calves from their dams. Cow-calf contact (CCC) systems may offer an alternative rearing solution that allows for the expression of natural behaviours, such as suckling and bonding. However, the effects of such systems on rest and lying behaviours of lactating cows are relatively unstudied. Cows are highly motivated to lie down, and a reduction in daily rest may have negative consequences for overall welfare. Thus, the aims of this study were: (1) to assess the effects of a CCC system on lying behaviours in lactating dairy cows, and (2) to determine if cubicle use of treatment dams and calves changes throughout the rearing period. Cow-calf pairs (n=37) were assigned 1 of 2 treatments after calving: dam-rearing (TREATMENT), where calves would be housed in the same facility as their dams, or separation shortly after parturition (CONTROL). Only TREATMENT cows had access to a modified lying area in which full CCC was available. Daily lying time – as well as the duration and frequency of lying bouts – was collected for cows automatically using leg-mounted tri-axial accelerometers (IceQube, IceRobotics, Edinburgh, UK). Video recordings were also collected and used to perform scan sampling at 10-minute intervals for a 24-h period each week. Behavioural data was collected during 14 weeks, starting when all cow-calf pairs had entered the experimental pen and continuing until weaning began. Access to full cow-calf contact did not affect lying behaviour. Overall, daily lying time and lying bout duration increased with consecutive time periods, while the frequency of lying bouts decreased. TREATMENT cows were observed to spend 76.6 ± 29.2% of their total lying time within the contact area across all weeks. These results combined indicate that lying behaviour in CCC systems is influenced by factors other than cow-calf contact, which cows are motivated to maintain throughout the rearing period.